2021
DOI: 10.21203/rs.3.rs-265487/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization of complementary and traditional medicine practitioners among older adults in India: results of a national survey in 2016-2017

Abstract: Background: Lack of information exists about the use of traditional and complementary medicine (TCM) use among older adults in India, which led to studying the estimates of past-12 month Ayurveda/Yoga/Naturopathy/Unani/Siddha/Homeopathy (AYUSH) and traditional health practitioner (THP) utilization in India. Methods: The study included 72,262 individuals (45 years and older) from the cross-sectional 2017-2018 Longitudinal Ageing Study in India (LASI) Wave 1.Results: The prevalence of past 12-month AYUSH practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, the scoring was reversed in the case of positive symptoms. The composite score ranged from 0 to 10, and those with a score of four or more were considered to have depression symptoms [ 45 , 46 ]. Cronbach’s alpha indicated that CES-D-10 has excellent reliability (0.8).…”
Section: Methodsmentioning
confidence: 99%
“…However, the scoring was reversed in the case of positive symptoms. The composite score ranged from 0 to 10, and those with a score of four or more were considered to have depression symptoms [ 45 , 46 ]. Cronbach’s alpha indicated that CES-D-10 has excellent reliability (0.8).…”
Section: Methodsmentioning
confidence: 99%